The Development and Symbolic Meaning of Pagatan Typical Woven Cloth Motifs in Manurung Village, Central Kusan District, Tanah Bumbu Regency - Fathurrahman, Fathurrahman; Yuliantri, Rhoma Dwi Aria; Noor, Muhammad (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This study discusses the development and symbolic meaning of the typical Pagatan woven fabric motifs produced in Manurung Village, Kusan Tengah District, Tanah Bumbu Regency. The method in this study uses a descriptive qualitative approach. Data were obtained through observation, interviews and documentation to identify the development of Pagatan woven cloth motifs occasionally. In addition, each motif's symbolic meaning is analysed to understand the message and cultural values contained in the typical Pagatan woven fabric. The results of the study show that the motifs of Pagatan woven fabrics have developed in line with the development of the knowledge of the weavers, changes in market tastes, community needs, and the influence of economic and social factors. Although experiencing growth, these motifs retain distinctive characteristics reflecting local wisdom and ancestral traditions. In addition, it was found that each motif has a deep symbolic meaning, including moral messages, traditional stories, and cultural values that describe the life of the people of Manurung Village.